A blueprint of the amino acid biosynthesis network of hemiascomycetes. Issue 7 (13th October 2014) - Förster, Jan; Halbfeld, Christoph; Zimmermann, Martin; Blank, Lars M.
Abstract The structure and regulation of biosynthesis pathways in Saccharomyces cerevisiae have been detailed extensively. For other hemiascomycetes, genomic sequences are primarily available, whereas biochemical information on them is scarce. The resulting biochemical networks that are used for research in basic science and biotechnology are often biased by data from S. cerevisiae, assuming that there are often implicitly conserved structures between species. We examined the structure of the amino acid biosynthesis network in nine hemiascomycetes, spanning the phylogenetic clade. Differences in the genetic inventory included the presence and absence of isoenzymes and compartmentation of the pathways. Notably, no two hemiascomycetes had identical genetic inventories. For example, the lack of the mitochondrial αIPMS isoenzyme and presence of only one copy of the BCAA aminotransferase in Pichia pastoris indicate a disparately compartmented leucine biosynthesis pathway. Our findings suggest that αIPMS and BCAA aminotransferase are solely located in the cytosol of P. pastoris, requiring correction of the leucine biosynthesis pathway layout in this species. Our results argue for careful use of information from S. cerevisiae and for joint efforts to fill the knowledge gaps in other species. Such analysis will lead to contributions in biotechnology disciplines, such as protein production and compartment engineering.